2005
DOI: 10.1105/tpc.105.035261
|View full text |Cite
|
Sign up to set email alerts
|

Sugars and Circadian Regulation Make Major Contributions to the Global Regulation of Diurnal Gene Expression in Arabidopsis  

Abstract: The diurnal cycle strongly influences many plant metabolic and physiological processes. Arabidopsis thaliana rosettes were harvested six times during 12-h-light/12-h-dark treatments to investigate changes in gene expression using ATH1 arrays. Diagnostic gene sets were identified from published or in-house expression profiles of the response to light, sugar, nitrogen, and water deficit in seedlings and 4 h of darkness or illumination at ambient or compensation point [CO 2 ]. Many sugar-responsive genes showed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
755
7
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 635 publications
(823 citation statements)
references
References 67 publications
47
755
7
14
Order By: Relevance
“…This implies hemicellulose degradation at low Suc levels and supports the idea of hemicellulose and cellulose mobilization to supply energy under Suc-limiting conditions (Contento et al, 2004;Hoch, 2007;Lee et al, 2007). Anticorrelation of profiles for several transcription factors and kinase genes with Suc levels supports the idea that the absence of Suc as the main energyproviding carbon molecule, rather than its presence, has an impact on cellular signaling (Blasing et al, 2005).…”
Section: Sugar Signaling Network May Cause Diurnal Regulation Of a Lsupporting
confidence: 56%
See 1 more Smart Citation
“…This implies hemicellulose degradation at low Suc levels and supports the idea of hemicellulose and cellulose mobilization to supply energy under Suc-limiting conditions (Contento et al, 2004;Hoch, 2007;Lee et al, 2007). Anticorrelation of profiles for several transcription factors and kinase genes with Suc levels supports the idea that the absence of Suc as the main energyproviding carbon molecule, rather than its presence, has an impact on cellular signaling (Blasing et al, 2005).…”
Section: Sugar Signaling Network May Cause Diurnal Regulation Of a Lsupporting
confidence: 56%
“…Hence, a significant fraction of those genes might act downstream of, or participate in, a sugar-dependent signaling cascade. In Arabidopsis seedlings, more than 4,000 diurnally fluctuating genes are affected by changing Suc levels and many of the rapidly Suc-induced or -repressed genes correlate either positively or negatively to diurnal Suc levels (Blasing et al, 2005;Osuna et al, 2007).…”
Section: Sugar Signaling Network May Cause Diurnal Regulation Of a Lmentioning
confidence: 99%
“…Similarly cellular sugar levels showed a major contribution in the establishment of diurnal gene expression patterns. 77 Interestingly these authors described that sugar-controlled gene expression was sensitive and responsive to low sugar levels, but not to high sugar. Through the study of the phosphoglucomutase (pgm) mutant, which impaired starch synthesis, they observed that when endogenous sugars levels diminished, sugar responsive genes were rapidly induced.…”
Section: Links Between the Plant Circadian Clock And Metabolismmentioning
confidence: 99%
“…Therefore in the wild type, transcriptional reprogramming to declining levels of sugars occurs at the end of the night. 77 It seems that the circadian clock and diurnal changes in carbon availability through photosynthesis are tightly linked and are responsible for many of the cyclic patterns of gene expression under natural day lengths.…”
Section: Links Between the Plant Circadian Clock And Metabolismmentioning
confidence: 99%
“…Essas enzimas são importantes em diferentes aspectos do metabolismo de sacarose além das relações de fonte e dreno como regulação osmótica e crescimento celular (Sturm & Tang 1999). Além disso, ao considerarmos que os carboidratos atuam não apenas como substrato para o metabolismo, mas também como moléculas sinalizadoras afetando a expressão de diversos genes (Rolland et al 2002, Blässing et al 2005, a importância da atividade de enzimas do catabolismo de sacarose pode ser estendida a diversos outros processos por possibilitar a alteração das concentrações locais de carboidratos.…”
Section: Resultsunclassified